ATP citrate lyase mediated cytosolic acetyl-CoA biosynthesis increases mevalonate production in Saccharomyces cerevisiae. Issue 1 (December 2016) - Rodriguez, Sarah; Denby, Charles; Vu, T.; Baidoo, Edward; Wang, George; Keasling, Jay
Abstract Background With increasing concern about the environmental impact of a petroleum based economy, focus has shifted towards greener production strategies including metabolic engineering of microbes for the conversion of plant-based feedstocks to second generation biofuels and industrial chemicals.Saccharomyces cerevisiae is an attractive host for this purpose as it has been extensively engineered for production of various fuels and chemicals. Many of the target molecules are derived from the central metabolite and molecular building block, acetyl-CoA. To date, it has been difficult to engineerS. cerevisiae to continuously convert sugars present in biomass-based feedstocks to acetyl-CoA derived products due to intrinsic physiological constraints—in respiring cells, the precursor pyruvate is directed away from the endogenous cytosolic acetyl-CoA biosynthesis pathway towards the mitochondria, and in fermenting cells pyruvate is directed towards the byproduct ethanol. In this study we incorporated an alternative mode of acetyl-CoA biosynthesis mediated by ATP citrate lyase (ACL) that may obviate such constraints. Results We characterized the activity of several heterologously expressed ACLs in crude cell lysates, and found that ACL fromAspergillus nidulans demonstrated the highest activity. We employed a push/pull strategy to shunt citrate towards ACL by deletion of the mitochondrial NAD+ -dependent isocitrate dehydrogenase (IDH1) and engineering higher flux through the upper mevalonate pathway. We demonstrated that combining the two modifications increases accumulation of mevalonate pathway intermediates, and that both modifications are required to substantially increase production. Finally, we incorporated a block strategy by replacing the native ERG12 (mevalonate kinase) promoter with the copper-repressible CTR3 promoter to maximize accumulation of the commercially important molecule mevalonate. Conclusion By combining the push/pull/block strategies, we significantly improved mevalonate production. We anticipate that this strategy can be used to improve the efficiency with which industrial strains ofS. cerevisiae convert feedstocks to acetyl-CoA derived fuels and chemicals.